Analisis Efektivitas Biaya Penggunaan Metformin dan Metformin- Glimepirid Pada Pasien Diabetes Melitus Tipe 2 di Dua Puskesmas Kulon Progo Yogyakarta: Mellitus Patients at the Two Public Health Centers Kulon Progo Yogyakarta Cost-Effectiveness Analysis of Metformin and Metformin-Glimepiride Use In Type 2 Diabetes - Lastrie, Astry; Dyah Aryani Perwitasar; Woro Supadmi (Indonesian Journal of Pharmacy and Natural Product, 2023)
Cost-effectiveness analysis (CEA) is a pharmacoeconomic method that is described in terms of cost-effectiveness ratios in order to assist decision making in selecting drugs that are effective in terms of benefits and costs. The purpose of this study was to determine the effectiveness of the use of metformin and metformin-glimepiride in type 2 DM patients at the 2 Public Health Centers Kulon Progo Yogyakarta. This analytical descriptive observational research employed a retrospective cohort design. The analysis was carried out by comparing the total costs incurred with the effectiveness of the therapeutic outcomes were obtained. The cost-effectiveness analysis of therapy used the Average Cost Effectiveness Ratio (ACER) and Incremental Cost Effectiveness Ratio (ICER) calculation methods. The results showed that the therapeutic effectiveness of the therapy used metformin and metformin-glimepiride in 12 patients (80%) and 30 patients (66.67%) respectively. The average cost of drugs from each group were Rp 9,072 and Rp 18,634. The ACER values were Rp 113.4 and Rp 279.5, respectively. The ICER value was obtained Rp – 717,3. The results of the chi-square test showed that there was no relationship between the type of therapy and the effectiveness of therapy (P=0.329) and the value of RR 2 with confidence interval (CI) 95% about 0.489-8.182. It can be concluded that based on the calculation of the ACER and ICER analysis methods, metformin therapy is more cost effective than metformin-glimepiride. There was no significant relationship between the type of therapy with the effectiveness of therapy. ABSTRAK Analisis efektivitas biaya (CEA) merupakan metode farmakoekonomi yang digambarkan dalam rasio biaya-efektivitas agar dapat membantu pengambilan keputusan dalam memilih obat yang efektif secara manfaat dan biaya. Tujuan dari penelitian ini untuk mengetahui efektivitas biaya penggunaan metformin dan metformin-glimepirid pada pasien DM tipe 2 di 2 Puskesmas Kulon Progo Yogyakarta. Metode penelitian yaitu observasional deskriptif menggunakan desain kohort retrospektif. Analisis dilakukan dengan membandingkan total biaya yang dikeluarkan dengan efektivitas outcome terapi yang didapatkan. Analisis efektivitas biaya terapi menggunakan metode perhitungan Average Cost Effectiveness (ACER) dan Incremental Cost Effectiveness Ratio (ICER). Hasil penelitian menunjukkan efektivitas terapi penggunaan metformin dan metformin-glimepirid secara berurutan sebanyak 12 pasien (80%) dan 30 pasien (66,67%). Biaya rata-rata obat dari masing- masing kelompok adalah Rp 9.072,- dan Rp 18.634,-. Nilai ACER secara berurut adalah Rp 113,4 dan Rp 279,5. Nilai ICER diperoleh Rp - 717,3. Hasil uji chi-square menunjukkan tidak ada hubungan antara jenis terapi dengan efektivitas terapi (P = 0,329) dan nilai RR 2 dengan konviden interval 95% berkisar antara 0,489-8,182. Dapat disimpulkan bahwa berdasarkan perhitungan metode analisis ACER dan ICER, terapi metformin lebih cost effective dibandingkan metformin-glimepirid. Tidak terdapat hubungan signifikan antara jenis terapi dengan efektivitas terapi.